Perancangan Pengalaman Pengguna Mobile Learning menggunakan Metode Human Centered Design (Studi Kasus: Madrasah Ibtidaiyah Hidayatul Athfal) - Agus Purnomo Ruminto; Riswan Septriayadi Sianturi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Covid-19 pandemic that has occurred since April 2020 has caused a change in online learning (offline) to online learning. Madrasah Ibtidaiyah Hidayatul Athfal is one of the elementary schools in Cinere, Depok city that is not ready to face the online learning process. Mobile-based online learning applications can help Madrasah Ibtidaiyah Hidayatul Athfal to organize an online learning process. This research aims to design the user experience to have good results in terms of user experience and usability. The method used in this research is Human Centered Design (HCD). HCD has 4 stages, namely identification of user context, specification of user requirements, design of solution design and evaluation of solution design. The user context identification stage was carried out by interviewing the Hidayatul Athfal Madrasah as a stakeholder. The second stage, the specification of user requirements is carried out by analyzing the results of interviews with stakeholders and users to obtain content requirements. The third stage, the design of the solution is carried out by implementing the results of the analysis and producing user flows, information architecture, wireframes, screenflows, mockups, and prototypes. The last stage is the evaluation of the solution design using the usability testing method and the User Experience Questionnaire (UEQ) to 10 respondents, namely 5 teachers and 5 students from Madrasah Ibtidaiyah Hidayatul Athfal. The design of the solution made obtained a score of 89.2% for the effectiveness aspect, 0.046 goals/second for the efficiency aspect, and 85.75 with grade A for the user satisfaction aspect. The UEQ results in the attractiveness aspect got the good category, perspicuity got the excellent category, efficiency got the good category, dependability got the good category, stimulation got the excellent category, and novelty got the above average category.